2010
DOI: 10.1590/s0074-02762010000600015
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic extracts of Leishmania braziliensis and Leishmania amazonensis associated with saponin partially protects BALB/c mice against Leishmania chagasi infection by suppressing IL-10 and IL-4 production

Abstract: This study evaluated two vaccine candidates for their effectiveness in protecting BALB/c mice against Leishmania chagasiinfection. These immunogenic preparations were composed of Leishmania amazonensisor Leishmania braziliensisantigenic extracts in association with saponin adjuvant. Mice were given three subcutaneous doses of one of these vaccine candidates weekly for three weeks and four weeks later challenged with promastigotes of L. chagasiby intravenous injection. We observed that both vaccine candidates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…In contrast to these reports, our study showed that saponin + LAg immunization not only failed to reduce parasite burden in liver of L. donovani challenged mice but also caused exacerbation of infection in spleen. These findings are partly in keeping with those of Grenfell et al , who observed that antigenic extracts of L. amazonensis or L. braziliensis in association with saponin conferred only partial protection against L. chagasi [29]. Thus, the efficacy of saponin with leishmanial antigens other than FML may vary, and such observations warrant further pre-clinical studies to establish the potential of saponin to adjuvant vaccines against leishmaniasis.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast to these reports, our study showed that saponin + LAg immunization not only failed to reduce parasite burden in liver of L. donovani challenged mice but also caused exacerbation of infection in spleen. These findings are partly in keeping with those of Grenfell et al , who observed that antigenic extracts of L. amazonensis or L. braziliensis in association with saponin conferred only partial protection against L. chagasi [29]. Thus, the efficacy of saponin with leishmanial antigens other than FML may vary, and such observations warrant further pre-clinical studies to establish the potential of saponin to adjuvant vaccines against leishmaniasis.…”
Section: Discussionsupporting
confidence: 85%
“…However, to our knowledge, our report represents the first observation that a saponin adjuvanted vaccine can induce robust IL-4. On the contrary, Greenfell et al , reported that vaccination with antigenic extracts of L. braziliensis and L. amazonensis associated with saponin resulted in reduced production of IL-4 [29]. There are few reports of low levels of IL-10 production [35] and a low ratio of IFN-γ/IL-10 producing T cells [28] with vaccination of FML antigen or its component formulated with saponin in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tested antigens were studied using the intravenous route of infection that guarantee the induction of VL but could undervalue the potential efficacy of some vaccines [44]. We decided to subcutaneously challenge L. chagasi in the footpad of BALB/c mice because this model has been accepted as an optimal screening tool to analyze protective antigens [45] and has been previously employed to test the immunoprophylactic properties of different parasite components [46,47], including the combination of LRP and saponin [15]. As it is shown in Figure  2C the L. chagasi challenge resulted in parasite active infection with the presence of parasites in the DLN (in the absence of footpad swelling) but also in the spleen and in the liver, internal organs involved in parasite replication in murine VL [48].…”
Section: Resultsmentioning
confidence: 99%
“…In accordance, mice vaccinated with the LmL3 + LmL5 + CpG-ODN combined vaccines showed a specific decrease in the LcSLA-mediated IL-10 ( P = 0.0004 for saline and P = 8 × 10 -7 for CpG-ODN) (Figure  3B) and also a controlled production of IL-4 specific for the parasite antigens ( P = 7 × 10 -5 for saline and P = 2 × 10 -5 for CpG-ODN) (Figure  3B) correlated to the presence of low levels of anti-LcSLA IgG1 reacting antibodies (Figure  5). Although the implication of IL-4 mediated responses in murine VL progression has not been clearly demonstrated, various reports have correlated the induction of protection against a subcutaneous challenge with L. chagasi to the control of Leishmania -specific IL-4 mediated responses [15,41,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…It is expected that an ideal vaccine against leishmaniasis will likely combine more than one antigen, and that antigens will preferentially be conserved among Leishmania species and present in both the amastigote and promastigote stages of the parasite (de Oliveira et al 2009;Grenfell et al 2010). The ideal candidates for vaccine prototype are the proteins required for parasite survival, which have low mutation rates and conserved epitopes (Nagill and Kaur 2010).…”
Section: New Perspectives For Applications Of Proteoliposomesmentioning
confidence: 99%